Ultimum Remedium to Increase Investor Interest in The Enforcement of Tax Criminal Sanctions in Indonesia: Case study PT VCI, Jakarta - Imam Nashirudin; Faisal Santiago (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2022)
Tax is the main source of state financing in Indonesia. To facilitate the implementation of the task of collecting state money, the Directorate General of Taxes requires easy, cheap and efficient ways. One of the efficient, easy and cheap ways is also applied in the handling of tax crimes. Research in this paper is legal research that is precritative and applied. The source of the material used is the primary legal material and the secondary legal material, by means of the study of the library/document, techniques a interconnected legal analysis to be drawn conclusions . The purpose of this research is to find out other legal efforts that can be taken by taxpayers to resolve tax criminal violations ,without going through a trial in court.. In this paper, the author will review the case of PT VCI and outline the legal basis that can be used to make administrative settlements for similar cases that have not been decided by the Judiciary. The result of this research has been known, that the submission of cassation legal efforts by the public prosecutor has been granted by the Supreme Court and the Supreme Court has sentenced the Director of PT VCI, Jakarta to 2 years imprisonment and paid a fine of 3 times the state's losses.